THE EVALUATION OF EFFECTIVE COMPLEX TREATMENT OF PATIENTS WITH GENERALIZED PARODONTITIS AND OSTEOPENIA - І.R. Yarmoshuk; M.M. Horns; L.І. Pelehan (Український стоматологічний альманах, 2018)
Abstract. Generalized periodontitis is a common disease. Its frequency increases with age and is characterized by inflammatory and resorption and destructive processes in the patient’s periodontal tissues. The issue of surgical treatment of patients with generalized periodontitis and osteopenia is particularly topical. Numerous studies have confirmed the benefits of surgical treatment procedures using osteoplastic material to stimulate repair process of periodontal tissues. The objective of the research was to improve the effectiveness of surgical treatment of patients with generalized periodontitis and osteopenia through the combined use of osteoplastic material and antiresorptive drugs in the preoperative and postoperative periods.